Recuperação de antocianinas do repolho roxo utilizando argilas como adsorvente - Guimarães, Darlyson Tavares (2019)
Anthocyanins are flavonoids that form one of the largest groups of pigments in the plant kingdom and are responsible for the red, blue and purple coloring of flowers and fruits. Although abundant in nature, several factors interfere with the stability of anthocyanins, making them very susceptible to degradation, which has become the focus of recent studies due to its potential applications in the food, pharmaceutical, cosmetic and medical industries. The purple cabbage (Brassica oleracea) is one of the most used sources of anthocyanins in food processing since they are highly acylated, presenting greater stability. Conventional anthocyanin extraction methods produce pigment solutions with large amounts of sugars and other byproducts that accelerate the degradation of this metabolite. Adsorption is a separation method which can be used for purification of anthocyanins, eliminating impurities by retaining them on the surface of an adsorbent. This work aims to carry out studies on the recovery of anthocyanins from purple cabbage through adsorption in clays (Sepiolite - SEP and Porous Clay Heterostructure – PCH. For this, the anthocyanins were extracted from the purple cabbage, as well as batch tests varying parameters to determine the best conditions for the natural recovery of the pigment. The vegetable extract was obtained through a mixture of ethanol, water and trifluoroacetic acid and quantified by the differential pH method, with an anthocyanin concentration of 40 mg. L-1. The highest adsorption levels occurred with adsorbent PCH, in mass of 25 mg and 120 minutes of contact, with 70% of adsorbed anthocyanins. With the eluent methanol, it was possible to recover 60% of the adsorbed anthocyanins. The SEP, under the same conditions, adsorbed 35% of the anthocyanins and allowed to recover 35% of these with the ethanol eluent. Both adsorbents showed good selectivity for the anthocyanins and little affinity with the sugars present in the extract, which are the main cause of the degradation of the pigment of interest. The analysis of anthocyanin samples in UPLC-QToF in the adsorption and desorption stages allowed the identification of six compounds of the class of cyanidines, all acylated. The highest affinity for clay occurred for anthocyanins with more than one organic acid in the structure, and this interaction was confirmed by FTIR analyzes.